2021
DOI: 10.4037/ajcc2021771
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of ICU Delirium Biomarkers and Their Alignment With the NIA-AA Research Framework

Abstract: Background Between 30% and 80% of survivors of critical illness experience cognitive impairment, but the underlying mechanisms remain unknown. Objective To determine whether intensive care unit (ICU) delirium biomarkers align with the National Institute on Aging–Alzheimer’s Association (NIA-AA) research framework for diagnostic biomarkers for Alzheimer disease and other related dementias (ADRD). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…54,55 A large meta-analysis of non-COVID survivors of critical illness has also identified associations of delirium with Aβ40, IL-6, and IL-1R antagonist. 56 Our study is unique in that we identified elevations across a spectrum of CNS specific markers, including neuronal (t-tau, UCHL1), and astrocytic/glial markers (GFAP), as well as AD-related markers (p-tau181).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…54,55 A large meta-analysis of non-COVID survivors of critical illness has also identified associations of delirium with Aβ40, IL-6, and IL-1R antagonist. 56 Our study is unique in that we identified elevations across a spectrum of CNS specific markers, including neuronal (t-tau, UCHL1), and astrocytic/glial markers (GFAP), as well as AD-related markers (p-tau181).…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, elevations in NfL have been associated with worse cognitive and functional outcomes in post‐operative patients and patients with septic encephalopathy 54,55 . A large meta‐analysis of non‐COVID survivors of critical illness has also identified associations of delirium with Aβ40, IL‐6, and IL‐1R antagonist 56 . Our study is unique in that we identified elevations across a spectrum of CNS specific markers, including neuronal (t‐tau, UCHL1), and astrocytic/glial markers (GFAP), as well as AD‐related markers (p‐tau181).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal protein aggregation (e.g., β-amyloid) can block the upstream within the cortical arteries and impair the external drainage of interstitial fluid in the deep white matter, thus contributing to the retrograde enlargement of PVS in CS ( Gouveia-Freitas and Bastos-Leite, 2021 ), and the relationship between β-amyloid accumulation and CS-PVS has been demonstrated in previous studies ( Roher et al, 2003 ; Charidimou et al, 2015 ). Furthermore, the impaired perivascular pathway may cause a vicious feed-forward cycle, further prompting PVS dysfunction and β-amyloid deposition in the vascular wall and brain ( Gouveia-Freitas and Bastos-Leite, 2021 ; Bown et al, 2022 ), which may exacerbate neurovascular dysfunction, neuroinflammation, and neurodegeneration ( Carrano et al, 2012 ; Parodi-Rullan et al, 2021 ), making the brain vulnerable to delirium ( Idland et al, 2017 ; Maldonado, 2018 ; Chan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…BG-PVS, basal ganglia perivascular space; CS-PVS, centrum semiovale perivascular space; CI, confidence interval. cause a vicious feed-forward cycle, further prompting PVS dysfunction and β-amyloid deposition in the vascular wall and brain (Gouveia-Freitas and Bastos-Leite, 2021;Bown et al, 2022), which may exacerbate neurovascular dysfunction, neuroinflammation, and neurodegeneration (Carrano et al, 2012;Parodi-Rullan et al, 2021), making the brain vulnerable to delirium (Idland et al, 2017;Maldonado, 2018;Chan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that surgery, in particular cardiac surgery, is associated with increased markers for neuronal damage and neurodegeneration, such as total-Tau and neuro lament light chain (NFL) [14][15][16][17]. In fact, these effects, including hypoxemia and disruption of the blood-brain barrier, seem to be caused by the entire procedure and not solely by inhalational anesthesia, as discussed earlier [18].…”
Section: Introductionmentioning
confidence: 99%